A Systematic Review of Empirical Evidence on Art Therapy With Traumatized Refugee Children and Youth - Annous, Nadia; Al-Hroub, Anies; El Zein, Farah (Frontiers in Psychology, 2022)
The current global refugee crisis revealed that refugee children, youth, and adults are uniquely vulnerable to traumatic events. Yet, there are only a few studies available that report robust systematic data on art therapy interventions with mental health in recent refugee populations. The purpose of the study is to synthesize and evaluate (a) the available research evidence on the use of art therapy in reducing post-traumatic stress disorder (PTSD) levels in refugees, and (b) the quality of empirical evidence for each of the reviewed studies. The authors adopted the Council for Exceptional Children (CEC) evidence-based practice (EBP) standards and quality indicators to evaluate the methodological soundness of the reviewed studies and the evidence-based classification of art therapy as a treatment intervention. We systematically searched electronic databases of pertinent review articles for the period from 2010 to 2020 using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Systematic searches identified 70 research articles but yielded eight eligible journals as per the inclusion criteria. Results indicated that, though considered a promising treatment approach, art therapy is presently classified as an intervention that falls under the category of practice with insufficient evidence. The findings suggest the need for further methodologically sound experimental studies to strengthen the evidence behind art therapy as an intervention to reduce PTSD symptoms in refugees around the world.